An eco-critical perspective on business models: The value triangle as an approach to closing the sustainability gap. (10th February 2018) - Biloslavo, Roberto; Bagnoli, Carlo; Edgar, David
Abstract: Despite business models having been discussed thoroughly by academics there are still some epistemological and ontological issues that have yet to be resolved. Business models seem to have stalled at the technological era and have not fully engaged with the era of sustainability. The purpose of our paper is to add a new lens and richness to sustainable business model research by building on the need for more interdisciplinary approaches. This paper applies an eco-critical approach to analyse the 20 most often cited business model frameworks. We explore the conventional understanding of the business models based on the language applied and reflect on gaps in the current perspectives of sustainability. The analysis shows that existing business model frameworks exclude natural and social aspects of organisational environment from the discussion and tend to neglect the interrelationships between economic and not-economic actors as well as the intertemporal trade-offs. Based on the results of the analysis we propose a new sustainable business model framework named "Value Triangle", which explicitly includes as core elements society incorporating the natural environment and future generations and three types of co-created and co-delivered value: public, partner and customer. The Value Triangle together with the corresponding canvas is presented through a business case for sustainability represented by Italian company Loccioni. The results show that the proposed business model framework and canvas allow managers to understand, analyse and evaluate their business models along all three dimensions of sustainability – economic, social, and environmental simultaneously. Such an understanding helps drive the field towards making a meaningful contribution to solving the UN global challenges and sustainability agenda. Highlights: Dominant business models have not kept pace with doing business in a sustainable way. Most business models define the borders of discussion in a way that excludes nature. Future development of business models is based on interdisciplinary areas of study. A value triangle for closing the business model sustainability gap is proposed. Business case for sustainability that supports best practice sharing is provided.